β-Blockers and Mortality After Acute Myocardial Infarction in Patients Without Heart Failure or Ventricular Dysfunction - Dondo, Tatendashe B; Hall, Marlous; West, Robert M; Jernberg, Tomas; Lindahl, Bertil; Bueno, Hector; Danchin, Nicolas; Deanfield, John E; Hemingway, Harry; Fox, Keith A A; Timmis, Adam D; Gale, Chris P (Journal of the American College of Cardiology, 2017)
For acute myocardial infarction (AMI) without heart failure (HF), it is unclear if β-blockers are associated with reduced mortality. The goal of this study was to determine the association between β-blocker use and mortality in patients with AMI without HF or left ventricular systolic dysfunction (LVSD). This cohort study used national English and Welsh registry data from the Myocardial Ischaemia National Audit Project. A total of 179,810 survivors of hospitalization with AMI without HF or LVSD, between January 1, 2007, and June 30, 2013 (final follow-up: December 31, 2013), were assessed. Survival-time inverse probability weighting propensity scores and instrumental variable analyses were used to investigate the association between the use of β-blockers and 1-year mortality. Of 91,895 patients with ST-segment elevation myocardial infarction and 87,915 patients with non-ST-segment elevation myocardial infarction, 88,542 (96.4%) and 81,933 (93.2%) received β-blockers, respectively. For the entire cohort, with >163,772 person-years of observation, there were 9,373 deaths (5.2%). Unadjusted 1-year mortality was lower for patients who received β-blockers compared with those who did not (4.9% vs. 11.2%; p < 0.001). However, after weighting and adjustment, there was no significant difference in mortality between those with and without β-blocker use (average treatment effect [ATE] coefficient: 0.07; 95% confidence interval [CI]: -0.60 to 0.75; p = 0.827). Findings were similar for ST-segment elevation myocardial infarction (ATE coefficient: 0.30; 95% CI: -0.98 to 1.58; p = 0.637) and non-ST-segment elevation myocardial infarction (ATE coefficient: -0.07; 95% CI: -0.68 to 0.54; p = 0.819). Among survivors of hospitalization with AMI who did not have HF or LVSD as recorded in the hospital, the use of β-blockers was not associated with a lower risk of death at any time point up to 1 year. (β-Blocker Use and Mortality in Hospital Survivors of Acute Myocardial Infarction Without Heart Failure; NCT02786654).